Bioinspired Structures: Collective Wetting of a Natural Fibrous System and Its Application in Pump‐Free Droplet Transfer (Adv. Funct. Mater. 22/2017). (June 2017) - Han, Yu Long; Li, Moxiao; Yang, Qingzhen; Huang, Guoyou; Liu, Hao; Qin, Yidan; Genin, Guy M.; Li, Feng; Lu, Tian Jian; Xu, Feng
Abstract : In article number1606607, Tian Jian Lu, Feng Xu, and co‐workers present a new wetting phenomenon derived from the strategy of dandelion seeds. Droplet capture and release are studied with respect to liquid properties and fiber geometry. Introducing a competitive liquid phase with smaller surface tension to the wetted fiber triggers droplet release. These results will benefit the design of responsive devices for droplet manipulation. Artwork: Moxiao Li.